Pemanfaatan Limbah Kayu Industri dan Kertas menjadi Lampu Dekoratif dengan Metode Learning by Doing - Setiati, Grace (Jurnal Aktual Pendidikan Indonesia, 2023)
One of the case studies in the Interior Product Design class is that students learn to use leftover industrial materials, namely wood and paper, into decorative works that have functional and aesthetic value. The aim of this lesson is to determine the effectiveness of the learning by doing method in optimizing the quality of designing student room accessories and to provide awareness to students about the importance of reprocessing waste into new creative works, namely interior accessories. Creation of work through a simple design thinking process, namely Inspiration, Ideation and Implementation and using the Learning by Doing method in the implementation process. The results obtained from this program are a creativity process using the learning by doing method which allows for direct learning experiences independently and collectively as well as a deeper understanding of the process of creating interior accessory works. Students also become skilled in processing wood and paper waste and are able to be creative by transforming wood and paper waste into decorative lamps for residential purposes.